2021
DOI: 10.1111/jfb.14933
|View full text |Cite
|
Sign up to set email alerts
|

Does tagging transparent fish increase predation risk? A laboratory study with glass eel (Anguilla anguilla) and sea bass (Dicentrarchus labrax)

Abstract: Barriers in the estuaries of the rivers prevent the immigration of glass eels (Anguilla anguilla) arriving on the European coast every spring. This leads to an unnatural accumulation of migrating glass eels below the barriers, and this may lead to additional losses in glass eels by piscivorous fish. The proportion of predation losses can be estimated using mark-recapture techniques and abundance estimates in combination with stomach content analysis of piscivorous fish. Nonetheless, whether tagging transparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Inland barriers without efficient fish passage could result in prolonged glass eel accumulations. Although limited information is available, predation and loss of condition, due to multiple unsuccessful attempts, might occur at these sites [ 58 60 ]. If glass eels fail to migrate to suitable habitats in the hinterland, glass eel might settle in the NSC.…”
Section: Discussionmentioning
confidence: 99%
“…Inland barriers without efficient fish passage could result in prolonged glass eel accumulations. Although limited information is available, predation and loss of condition, due to multiple unsuccessful attempts, might occur at these sites [ 58 60 ]. If glass eels fail to migrate to suitable habitats in the hinterland, glass eel might settle in the NSC.…”
Section: Discussionmentioning
confidence: 99%
“…Mark-recapture techniques are present in various forms and differences among these methods include group (mass) or individual marking, tag retention and the necessity to kill glass eels to identify recaptures. Examples are methods such as alizarin red S (Kullmann et al 2017, Kullmann et al 2018, Diekmann et al 2019, oxytetracycline (Simon and Dörner 2005), vital dyes (Briand et al 2005), coded wire tags (Simon and Dörner 2005), PIT tags ) and visible implant elastomer (VIE) tags (Imbert et al 2007, Griffioen et al 2022a) are all used in the field for various purposes. To answer the research questions of passage success (Q2) and bottleneck analysis (Q3), marking method that can discriminate between groups, affecting neither behaviour nor survival, are preferred.…”
Section: Mark Recapture Techniquesmentioning
confidence: 99%
“…Small eels have been successfully tagged with visible implant elastomers (VIE) (Simon & Dörner, 2011) and coded wire tags (CWTs) (Thomassen et al, 2000;Jepsen et al 2010). Griffioen et al (2022) found that marking glass eels with VIE did not lead to increased predation.…”
mentioning
confidence: 99%
“…Griffioen et al . ( 2022 ) found that marking glass eels with VIE did not lead to increased predation. Although these methods work well, their use is limited to situations where the eels are recaptured.…”
mentioning
confidence: 99%